Glamour : Fashion + Industrial Design + Architecture. - Benezra, Neal; Keffer, Ruth; Patton, Phil; Postrel, Virginia; Rosa, Joseph; Steele, Valerie (London San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2004)
Adrian ; Arad, Ron ; Balenciaga, Cristobal ; Becket, Welton ; Blaisse, Petra ; Boontje, Tord ; Bouroullec, Erwan ; Bouroullec, Ronan ; Bunshaft, Gordon ; deCOi ; Denari, Neil ; Diaz Alonso, Hernán ; Dickinson, John ; Dior, Christian ; Dolce & Gabbana ; Van Duysen, Vincent ; Emergent ; Fath, Jacques ; Frey, Albert ; Galanos, James ; Galliano, John ; Gaultier, Jean Paul ; Grcic, Konstantin ; Haas, Brent ; Haines, William ; Harrison, Wallace ; Herzog & de Meuron ; Jacobs, Marc ; Jakob + MacFarlane ; Johnson, Philip ; Koolhaas, Rem ; Lacroix, Christian ; Lagerfeld, Karl ; Lapidus, Morris ; Laurent, Yves Saint ; Lovegrove, Ross ; Luckman, Charles ; Lynn, Greg ; Madame Grès ; Martin, Albert C. ; Mayer Hermann, Jürgen ; McQueen, Alexander ; Mugler, Thierry ; Naden, Mark ; Neff, Wallace ; Newson, Mark ; Patterns/Marcelo Spina ; Posen, Zac ; Prada ; Pucci, Emilio ; Rabanne, Paco ; Rapson, Ralph ; Rath, Hans Harald ; Reinhold, John ; Rolex ; Rudolph, Paul ; Sanders, Joel ; Sant'Angelo, Giorgio di ; Saunders, Jonathan ; Sayer, Malcolm ; Stone, Edward Durell ; Tschumi, Bernard ; Versace, Donatella ; Versace, Gianni ; Westwood, Vivienne ; Yamasaki, Minoru
As one of the most alluring yet elusive concepts in contemporary style, glamour is an ideal that permeates our visual culture. Published to coincide with an exhibition at the San Francisco Museum of Modern Art, this catalogue radically revises our understanding of glamour in the fields of fashion, industrial design, and architecture. Tracing glamour's trajectory from Hollywood's golden age to its present day connotations of affluence, this lavishly illustrated volume presents a striking array of postwar couture, jewelry, automobiles, furniture, and built and unbuilt architecture - all of which share an affinity for richly decorative patterning, complete layering, and sumptuous materials.
Glamour : Fashion + Industrial Design + Architecture, SFMOMA (San Francisco Museum of Modern Art), San Francisco, 2004-10-09. 2005-01-17
boek